Rebounds after discharge from the emergency department for community-acquired pneumonia: focus on the usefulness of severity scoring systems - Ferrari, Rodolfo; Viale, Pierluigi; Muratori, Paolo; Giostra, Fabrizio; Agostinelli, Daniela; Lazzari, Roberto; Voza, Riccardo; Cavazza, Mario (Acta Biomedica Atenei Parmensis, 2018)
Background: Community-acquired pneumonia (CAP) is common cause of hospital admission and leading cause of morbidity and mortality. Severity scoring systems are used to predict risk profile, outcome and mortality, and to help decisions about management strategies. Aim of the work and Methods: To critically analyze pneumonia “rebound” cases, once discharged from the emergency department (ED) and afterwards admitted. We conducted an observational clinical study in the acute setting of a university teaching hospital, prospectively analyzing, in a 1 year period, demographic, medical, clinical and laboratory data, and the outcome. Results: 249 patients were discharged home with diagnosis of CAP; 80 cases (32.1%) resulted in the high-intermediate risk class according to CURB-65 or CRB-65. Twelve patients (4.8%) presented to the ED twice and were then admitted. At their first visit 5 were in the high-intermediate risk group; just 4 of them were in the non-low risk group at the time of their admission. The rebound cohort showed some peculiar abnormalities in laboratory parameters (coagulation and renal function) and severe chest X-rays characteristics. None died in 30 days. Conclusions: The power of CURB-65 to correctly predict mortality for CAP patients discharged home from the ED is not confirmed by our results; careful clinical judgement seems to be irreplaceable in the management process. Many patients with a high-intermediate risk according to CURB-65 can be safely treated as outpatients, according to adequate welfare conditions; we identified a subgroup of cases that should worth a special attention and, therefore, a brief observation period in the ED before the final decision to safely discharge or admit.